Psychosocial risks prevention: Perspectives from Portuguese SMEs - Ramos, S.; Costa, P.; Silva, S.; Passos, A.; Tavares, S. (12th EAOHP Conference. Occupational health psychology in times of change: Society and the workplace, 2016)
Introduction: This paper presents the Portuguese results from the first phase of the PPPSER project, which has a qualitative nature. Micro, small and medium enterprises (SMEs) represent 99.9% of the Portuguese business setting. According to national sources, there are 1,167,811 SMEs in Portugal, with a combined turnover of 220 billion euros. Therefore, the main goal of this phase was to gather data from relevant SMEs stakeholders about what they perceived as psychosocial risks, their main causes and consequences, the general level of awareness about the issue, the main obstacles to prevention and intervention and specific actions developed considering those risks.